Profile Albumin and Beta Carotene Formula Instant Baby Porridge - Dewi Kartika Sari; Ali Rosidi; Hafni Rahmawati (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Complementary feeding of breast milk should be given to infants after 6 months to increase nutritionalneeds. Instant baby porridge is known as one of complementary feeding of breast milk which is hygienic,easy to serve, and known by. Protein and vitamin A from snakehead fish (Ophiocephalus striatus) meal andpumpkin (Cucurbita moschata) flour can be used to improve the nutrition content of baby porridge . Thepurpose of this study was to determine the albumin and beta-carotene profiles of instant baby porridgesubstituted by 15 and 20% of snakehead fish meal and 10 and 15% of yellow pumpkin flour. Preparationof instant baby porridge carried out bydry mixing method. All ingredients wereapplied indriy condition,then mixed according to the standard of the formula of MP-ASI. The appearance ofinstant baby porridgewas yellowness and ready to eat after brewed with hot water (±60oC) with a ratio of 1 : 1. The results showedthat t instant baby porridge with 20% of snakehead fish meal and 15% of pumpkin flour substitution has thehighest albumin and beta carotene profiles which the value were 2.20% and 3.40 mg/100 g or 283.33 μg/100g vitamin A, respectively.